Storytelling in Digital Branding Through the Nuance of the English Language for Global Market Penetration - Pramesti, Puji (Program Studi Administrasi Bisnis, 2025)
In the evolving landscape of global digital marketing, storytelling has emerged as a powerful strategy for building emotional connections between brands and consumers. This study explores how multinational companies utilize English-language storytelling to engage international audiences while balancing the demands of cultural localization and brand consistency. Through a qualitative content analysis of 30 storytelling artifacts from Nike, Dove, and Airbnb, the research examines the linguistic and narrative techniques employed across global and regional campaigns. Findings reveal that while English serves as a unifying medium for brand identity, culturally adapted narratives significantly enhance audience engagement, particularly in non-Western markets. Brands that localized their storytelling—through idiomatic expressions, culturally resonant metaphors, and region-specific visuals—achieved higher interaction rates and stronger emotional resonance. The study concludes that effective digital branding requires a nuanced understanding of language and culture, even within a global lingua franca like English. Recommendations for future research include investigating non-English dominant markets, platform-specific storytelling strategies, and the impact of AI-driven personalization on narrative authenticity. This research contributes to the growing discourse on intercultural communication, digital marketing, and the strategic use of English in global branding.